Pediatric Olecranon Fracture with Coronoid Process Osteochondral Flap Fracture: A Rare and Challenging Case - Chong, Jung Syn; Abdul Aziz, Aziah; Raghunandanan, Shashank; Kamaludin, Nur Azuatul Akmal; Mohd Termizi, Nur Syahida (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: Osteochondral flap fracture is a variant of fracture in the pediatric age group. It is caused by a shearing force that separates the articular cartilage from the underlying subchondral bone. We present a pediatric case of an olecranon process fracture with an osteochondral flap fracture of the coronoid process. Case report: A 10-year-old child presented with swelling and pain in the right elbow after an incident of direct trauma. A plain radiograph revealed multiple small fracture fragments, inconclusive of coronoid process involvement. Intraoperatively, we found an osteochondral fracture of the coronoid process with anteromedial facet displacement. The fracture was reduced and secured with two K-wires. The undisplaced olecranon fracture was fixed with a K-wire in situ. Conclusions: Osteochondral flap fractures of the coronoid process can be easily missed and underestimated in imaging studies. Neglected fractures can lead to severe impairment of elbow motion and function and cause chronic pain. The anatomical reduction of the coronoid facet is crucial and yields the best outcome.